Increasing event‐driven HIV pre‐exposure prophylaxis use among gay, bisexual and other men who have sex with men in Australia: results from behavioural surveillance 2019–2023 - Curtis Chan; Martin Holt; Anthony K. J. Smith; Timothy R. Broady; James MacGibbon; Limin Mao; Ben Wilcock; John Rule; Benjamin R. Bavinton (Journal of the International AIDS Society)
Abstract Introduction HIV pre‐exposure prophylaxis (PrEP) has been publicly available since 2018 in Australia as a daily regimen. In 2019, clinical guidelines were updated to support guidance on event‐driven PrEP (ED‐PrEP) use. We assessed trends in the PrEP dosing regimen by comparing daily PrEP use to ED‐PrEP among cisgender gay, bisexual and other men who have sex with men (GBMSM). Methods Data from repeated, cross‐sectional, national behavioural surveillance surveys were analysed from 2019 to 2023 among participants not living with HIV. Logistic regression models were conducted to assess trends and compared ED‐PrEP users to non‐PrEP users and daily PrEP. Results Among 38,880 participants, overall PrEP use with any regimen increased from 27.6% in 2019 to 42.7% in 2023 (OR = 1.16, 95% CI = 1.15−1.18, p < 0.001). Among 12,922 participants who reported PrEP use in the last 6 months, the proportion reporting ED‐PrEP use increased from 7.6% in 2019 to 27.8% in 2023 (OR = 1.41, 95% CI = 1.37−1.46, p < 0.001) with those who reported daily PrEP decreasing from 92.4% to 63.3% (OR = 0.64, 95% CI = 0.62−0.66, p < 0.001). In a cross‐sectional sub‐sample in 2022–2023 (n = 8840), compared to ED‐PrEP users, non‐PrEP users were less likely to have received three or more HIV tests in the last 12 months (aRRR = 0.26, 95% CI = 0.22−0.31, p < 0.001), have 2−10 male sexual partners in the last 6 months (aRRR = 0.24, 95% CI = 0.14−0.41, p < 0.001) or 11 or more (aRRR = 0.26, 95% CI = 0.15−0.45, p < 0.001) compared to none, or to report condomless anal intercourse with casual partners (aRRR = 0.38, 95% CI = 0.32−0.46, p < 0.001). Compared to ED‐PrEP users, daily PrEP users were more likely to have received three of more HIV tests in the last year (aRRR = 3.73, 95% CI = 3.15−4.40, p < 0.001) and less likely to be born overseas and lived in Australia for less than 5 years compared to being born in Australia (aRRR = 0.64, 95% CI = 0.49−0.83, p = 0.001). Conclusions While daily PrEP remains the most common PrEP dosing regimen among GBMSM in Australia, there has been a steep increase in the proportion of PrEP users who are taking ED‐PrEP. Monitoring of PrEP use should continue to adapt to new dosing methods and future PrEP options. As ED‐PrEP use increases, further work is needed to ensure those taking ED‐PrEP are taking it effectively to prevent HIV.